Politik Pendidikan Islam Masa Modern; Membaca Gagasan Tokoh Pembaharu di Negara Turki, India, dan Mesir - Zainur Arifin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
In the middle of the fight and friction of ideas in the early 20th century Mustafa Kemal emerged a prominent Turkish Nationalists and the new leader who managed to expel Greece from Turkey. Furthermore, thanks to the leadership talent and brilliance of his political ideas, he managed to be proclaimed Turkish Republic and he was elected as a President of the first by the Grand National Assembly. Ahmad Khan in India got a traditional upbringing in religious education. His formal education ended when he was 18 years old. His political activities is the struggle to defend the Muslims of British accusations after the uprising of 1857. By convincing the British that Islam does not play a major role in the uprising, but due to British intervention in the matter of religion. Taha Husein one reformer in the Egyptian thinker who saw the need for Egypt to learn from Europe as well take the culture if Egypt wants advanced and powerful. This idea was initially considered controversial and have not been received at the time of Egyptian society, including intellectuals. As well regarded as the idea of ​​secularization that have come out of Islam